2016
DOI: 10.5964/ejop.v12i2.1097
|View full text |Cite
|
Sign up to set email alerts
|

Empathy, guilt proneness, and gender: Relative contributions to prosocial behaviour

Abstract: Guilt is a moral emotion that is often looked upon as a negative trait. However, studies show that some individuals are more predisposed to think, feel and act in a more ethical manner because of a lower threshold to experience guilt. Some theories of helping behaviour emphasize the evolutionary mechanisms, while other theories stress the importance of social variables. This study investigated whether guilt proneness as a dispositional trait can be associated with prosocial behaviour. Five hundred sixty-nine p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 23 publications
3
15
0
3
Order By: Relevance
“…In line with the results of previous studies (e.g., Torstveit, Sütterlin & Lugo, 2016), we found higher levels of guilt in females than in males. We believe that this may be because females tend to be more empathic than men, which is true in this sample too.…”
Section: Discussionsupporting
confidence: 93%
“…In line with the results of previous studies (e.g., Torstveit, Sütterlin & Lugo, 2016), we found higher levels of guilt in females than in males. We believe that this may be because females tend to be more empathic than men, which is true in this sample too.…”
Section: Discussionsupporting
confidence: 93%
“…The negative relationship between narcissism and guilt proneness may be related to the lack of empathy and excessive sense of entitlement which often characterizes narcissism ( American Psychiatric Association, 2013 ). According to other studies, guilt proneness is positively correlated to empathy ( Torstveit et al, 2016 ; Xu et al, 2012 ). Individuals who are high in narcissism usually report negative associations to empathy, and it may reflect their inability to take other individual's emotional state, which also often may lead to antisocial behaviour ( Delič, Novak, Kovačič, & Avsec, 2011 ; Eisenberg, 2007 ; Karremans, Van Lange, & Holland, 2005 ; Vonk, Zeigler-Hill, Mayhew, & Mercer, 2013 ).…”
Section: Discussionmentioning
confidence: 72%
“…Lack of moral emotions such as guilt and shame might provide a possible reason for the observed maladaptive behaviour. A growing body of research supports the notion that individuals who are more inclined to ethical behaviours often show a lower threshold for experiencing guilt ( Cohen, Panter, & Turan, 2012 ; Katchadourian, 2010 ; Torstveit, Sütterlin, & Lugo, 2016 ). Moral emotions play a crucial role in deterring unethical and antisocial behaviour ( Olthof, 2012 ; Xu, Bègue, & Bushman, 2012 ).…”
Section: Narcissism and Moral Emotionsmentioning
confidence: 99%
“…Furthermore they also concluded that increased feelings of guilt can explain greater subjective weight, rather than feelings of disgust, pride, or sadness. (Torstveit, Sütterlin, & Lugo, 2016) demonstrated how guilt proneness combined with empathy explained additional variance in prosocial behavior. The findings were that there are gender differences in guilt proneness explaining prosocial behaviour.…”
Section: Guiltmentioning
confidence: 99%